Analisis Bentuk Metafora Lirik Lagu dalam Album Yang Patah Tumbuh, Yang Hilang Berganti Karya Banda Neira - Ike Azhani Putri; I Ketut Darma Laksana; I Gusti Ngurah Ketut Putrayasa (Udayana University, 2022)
Humans express in two ways, namely verbal and nonverbal. Song is a form of nonverbal linguistic expression. Through songs, various meanings can be created from the beauty of its structure. One of the aesthetic elements in the song is metaphor. Based on this, this research is entitled